POLLUTION PREVENTION (P2) INDUSTRY - Inche Mitma, Jorge Luis (1998)
The pollution prevention (P2) involves the use of materials, processes, or practices that reduce or eliminate the generation of pollutants or wastes at the source, ie in the same industry. Avoiding waste, companies eliminate the problems of treatment and disposal, which saves them money and allows them to focus on their core objectives of providing goods or services ...